Positioning in a Primary Writing Workshop: Joint Action in the Discursive Production of Writing Subjects - Bomer, Randy; Laman, Tasha (Research in the teaching of English, 2004)
Drawn from a year-long study in a combined first- and second-grade classroom, this article presents an interpretive portrait of two young students engaged in spontaneous talk while writing. We analyze their conversations to explore the subject positions these student writers assumed, those they assigned each other, and the related functions they assigned the texts they composed. Through our close reading of their conversations, we develop an analytic protocol for positional microanalysis of everyday conversations that honors the intertwined social and emotional dimensions of peer interactions. Countering those who would cast literacy development as the sequential attainment of discrete cognitive skills, we consider the ways that these social and emotional dimensions may interlace with intellectual growth as young children struggle to become students, writers, and people.